Development of an IT project "Logistics" based on cloud technology - Ye. V. Maher; F. V. Rud; B. L. Tkachenko; V. V. Fialkovskyi; Y. V. Tryus (Academy of Cognitive and Natural Sciences, 2013)
Among the ways to improve the quality of training of future IT specialists with higher education, to intensify academic-cognitive and research activities of students, to reveal their creative potential, to increase the role of independent and individual work, to increase their competitiveness in the IT market we can highlight the development of educational IT projects and start-ups using cloud services In order to use innovative ICT in training of future IT specialists, as well as to implement the abovementioned approach, IT project "Logistics" is being developed at Cherkasy State Technological University at the Faculty of Information Technologies and Systems.